Managing Thrips in Pepper and Eggplant - Joe Funderburk; Stuart Reitz; Phil Stansly; Dave Schuster; Greg Nuessly; Norm Leppla (EDIS)
Revised! ENY-658, a 10-page illustrated fact sheet by Joe Funderburk, Stuart Reitz, Phil Stansly, Dave Schuster, Greg Nuessly, and Norm Leppla, provides pepper and eggplant growers with management information for this serious pest of ornamental, vegetable, and fruit crops in the field and greenhouse — biology and ecology, tomato spotted wilt, and management programs. Includes references. Published by the UF Department of Entomology and Nematology, October 2009.